Chapter 9. HZPC Americas Corporation Early-Line Variety Trial, 2006 - Chad M. Hutchinson; Doug Gergela (EDIS)
This is a multi-chapter report by C.M. Hutchinson and Doug Gergela. In the process of being published by the UF Department of Horticultural Sciences, January-July 2007.